2004
DOI: 10.1152/ajpregu.00465.2003
|View full text |Cite
|
Sign up to set email alerts
|

Blunted hypothalamic neuropeptide gene expression in response to fasting, but preservation of feeding responses to AgRP in aging male Brown Norway rats

Abstract: Aging mammals lose the ability to maintain energy balance, exhibiting decreased appetite (anorexia) and impaired ability to maintain body weight. To determine the contribution of hypothalamic neuropeptides, two experiments were performed in male Brown Norway rats. To assess the hypothalamic neuropeptide response to food deprivation, young (Y; 4 mo old), middle-aged (M; 13 mo), and old (O; 25 mo) rats were either ad libitum fed or fasted for 72 h (n = 10/group) and killed. Hypothalamic levels of agouti-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 63 publications
0
43
0
Order By: Relevance
“…Its anorexigenic activity results from the inhibition of NPY neurons. Results for agerelated changes are inconclusive: some authors reported increased CART mRNA expression ( Wolden-Hanson et al 2004), while others found no changes (Kappeler et al 2003). As shown by Sohn et al, testosterone may lower hypothalamic CART mRNA levels (Bender et al 2014).…”
Section: Cocaine-and Amphetamine-regulated Transcriptmentioning
confidence: 96%
See 2 more Smart Citations
“…Its anorexigenic activity results from the inhibition of NPY neurons. Results for agerelated changes are inconclusive: some authors reported increased CART mRNA expression ( Wolden-Hanson et al 2004), while others found no changes (Kappeler et al 2003). As shown by Sohn et al, testosterone may lower hypothalamic CART mRNA levels (Bender et al 2014).…”
Section: Cocaine-and Amphetamine-regulated Transcriptmentioning
confidence: 96%
“…Results of studies on changes in NPY secretion with aging are inconclusive. NPY mRNA expression declines with aging in rats ( Wolden-Hanson et al 2004) and older rats show altered feeding responses to NPY (Blanton et al 2001). It has been found that aging decreased the feeding and drinking effects of NPY in rats (Pich et al 1992), but not in mice (Morley et al 1987).…”
Section: Neuropeptide Ymentioning
confidence: 99%
See 1 more Smart Citation
“…CART peptide expression is stable through adulthood hypothalamic expressions of numerous orexigenic neuropeptides such as npy, agRp and orexins were changed during aging, however, expression of the anorexigenic neuropeptide pomC was similar in young and old animals [13,14,26,28,34]. in the arcuate nucleus of aging animals, decrease of npy expression was detected, which coincided by an increase of CaRt expression [34].…”
Section: The Ages Of the Animalsmentioning
confidence: 96%
“…decreased expression of agouti-related peptide (agRp) and neuropeptide y (npy) genes was demonstrated in the hypothalamic arcuate nucleus with the age, and very old animals have shown increased sensitivity for agRp compared to younger animals [34]. in contrast, npy had a stronger effect on food intake in younger rats than in aged animals [2,8].…”
mentioning
confidence: 99%